AFFILIATES IN THE ERA OF SOCIAL COMMERCE: A COMPARATIVE REVIEW OF INDONESIAN LAW AND ISLAMIC ECONOMIC LAW - Mansyuroh, Firqah Annajiyah; Ibrahim, Nur Yudha (Al-Adl : Jurnal Hukum, 2025)
Social commerce is doing product business through social media. The latest example is the Indonesian TikTok shop with an affiliate system. In this system, partners promote products without having product inventory. They only provide information in the form of photos, videos, and purchase links. This system allows partners to earn money just by promoting other people's products, without requiring a lot of business costs. However, there is also a downside, namely that if consumers ask for more information, affiliates often cannot answer because they do not have full control over the products being sold. This is considered to violate the legal provisions of buying and selling in Islamic economics because the product information provided may not be clear. This type of research is normative legal research and a comparative approach. This research was carried out by investigating library materials, such as business law in Indonesia and MUI fatwa regulations. The results of this research indicate that according to Indonesian positive law and Islamic economics, the use of an affiliate system as a marketing tool is considered halal if it follows Islamic principles. However, differences were found in these two laws, namely that the method of giving punishment to users who violate the law is very clearly regulated by positive law, whereas because this is a contemporary case there is no clarity in Islamic economic law.